Multiparameter Measurement in Ethylene Diffusion Flame Based on Time-Division Multiplexed Tunable Diode Laser Absorption Spectroscopy - Haibin Cui; Fei Wang; Qunxing Huang; Jianhua Yan; Kefa Cen (IEEE Photonics Journal, 2019)
An optical method for measuring soot volume fraction, flame temperature, and concentration of combustion products in a diffusion flame based on time-division multiplexed tunable diode laser absorption spectroscopy technique is presented in this article. By moving the slot burner with an electric platform, two-dimensional profile of soot volume fraction, flame temperature, and gas concentrations along the flame sheet with 1-mm spatial resolution were obtained simultaneously. The flame temperature and soot volume fraction were simultaneously on-line monitored using one distributed feedback diode laser with a center wavelength at 1397.83 nm. Tunable diode laser absorption spectroscopy based temperature measurements in the flame were carried out by two-line thermometry of H2O and compared with the thermocouple technique. The attenuation of tunable diode laser intensity caused by soot extinction and gas absorption after transmitting through the diffusion flame was detected. And the soot volume fraction was determined quantitatively with laser extinction based on Rayleigh limit assumption. Two tunable distributed feedback diode lasers with center wavelength at 2001.6 and 2302 nm were used to determine the CO2 concentration and CO concentration, respectively. The experimental results of soot volume fraction, flame temperature, and the mole fraction of combustion products by varying concentrations of CO2 added in the diffusion flame were analyzed.